Theoretical Calculation and Experimental Studies of Boron Phosphide Polycrystalline Synthesized at High Pressure and High Temperature - Peng Yang; Ziwei Li; Haidong Yu; Shan Gao; Xiaopeng Jia; Hongan Ma; Xilian Jin (Nanomaterials)
In this study, a combination of theoretical calculations and experiments were carried out to analyze boron phosphide materials. Amorphous boron powder and amorphous red phosphorus were used as raw materials to directly synthesize the target samples in one step under high-pressure and high-temperature (HPHT) conditions. Theoretical calculations were then carried out based on the XRD spectra of boron phosphide at 4 GPa and 1200 °C. The experimental results show that the target samples can be successfully prepared at HPHT. The electrical properties of the samples were characterized, and it was found that their conductivity increased with the increase in temperature, and they have a semiconducting nature, which is consistent with the theoretical calculations. Its Seebeck coefficient is positive at different temperatures, indicating that the synthesized boron phosphide is a P-type semiconductor. The combination of theoretical calculations and experiments shows that high pressure can reduce the lattice constant of boron phosphide, thus reducing its forbidden bandwidth, which improves its electrical properties. EDS shows a homogeneous distribution of the elements in the samples. Successful synthesis of BP crystals will probably stimulate more research into its semiconductor properties. It may also provide some assistance in the application of BP in aero-engine high-temperature monitoring systems as well as thermally controlled coatings for deep-space probes.